Analisis Gaya Komunikasi Presenter Dalam Penyampaian Berita Pada Program Patroli Files di Akun Tiktok @patroli.indosiar - Dalimunthe, Rehana Salsabila (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
Every individual requires continuous information for complete understanding. The media industry and its professionals, including presenters, are responsible for delivering news effectively. In conventional media, the communication style of presenters tends to be formal, static, and adheres to broadcasting standards. However, the digital era, particularly platforms like TikTok, has transformed how society accesses news. Presenters now adjust their communication style to suit TikTok's characteristics and audience. One example is the Patroli Files program on TikTok account @patroli.indosiar, where presenters maintain a professional style but with a more expressive and dynamic approach compared to the rigid and less expressive style of conventional media. This study aims to analyze the communication style of presenters in delivering news on the Patroli Files program on TikTok account @patroli.indosiar. The research uses a descriptive qualitative method, with data collection techniques including observation and documentation. Data analysis applies Miles and Huberman's model, encompassing data reduction, data display, and conclusion drawing. The theory employed is Robert Norton’s communication style theory, which includes ten categories with specific indicators. The findings indicate that the presenters’ communication style in the Patroli Files program is flexible, adapting arrangement, intonation, and gestures to the platform’s characteristics. They predominantly use seven out of ten communication styles from Robert Norton: dominant, dramatic, contentious, animated, impressive, open, and precise, making the news delivery engaging, dynamic, and memorable. In contrast, relaxed, attentive, and friendly styles are rarely observed, as the serious, professional, and informative nature of the news prevails, setting apart TikTok’s expressive style from conventional media’s rigidity.